EMPOWERING MSMES IN UTTAR PRADESH: PERFORMANCE, CHALLENGES, AND FUTURE PROSPECTS - Saxena, Sonakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economic development of Uttar Pradesh (UP), one of India’s most populous and industrially diverse states. This paper analyzes the performance of MSMEs in UP, focusing on their contribution to the state's economy, employment generation, and sectoral growth. Despite their significant role, MSMEs face numerous challenges such as inadequate infrastructure, limited access to finance, and technological barriers. The paper also evaluates government policies and schemes aimed at promoting MSME growth and provides policy recommendations to enhance the sector’s competitiveness.